Advancing Government Legitimacy through the Scientific Study of Sentience. Issue 5 (4th July 2021) - Freeling, Benjamin S.; Connell, Sean D.
Abstract: The ongoing crises in environment and public health have uncovered an opportunity for innovation. Yet, if we are serious about improving the human and more-than-human natural worlds, societies and institutions need a new mindset. One potential mindset is offered by the emerging science of animal sentience, defined as the capacity to feel emotion, pleasure and pain. The study of sentience has revealed a contradiction at the heart of government legitimacy, and a solution. This solution provides a vision of a society where the interests of all sentient organisms are enshrined in our institutions, providing a more robust and sustainable society.